INTEGRASI LITERASI SAINS DAN NILAI-NILAI AKHLAK DI ERA GLOBALISASI - Fajar Dwi Mukti (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2018)
The era of globalization has had quite a broad impact on various aspects of life, especially in the provision of education, so students' scientific literacy which includes knowledge of science, science processes, development of scientific attitudes, and students' understanding of science can be integrated with moral values. The method in this study is a literature review that discusses the importance of integrating scientific literacy and moral values ​​in the era of globalization. Solutions to be able to overcome various problems of the globalization era that occur both political, economic, social and cultural problems as well as problems of moral and intellectual decadence especially among students, it is necessary to strengthen moral values ​​and scientific literacy.